(3QHhGJ GdbQV hQHhGJ GdHjY (B/s - (3Jhajb QVG, MSjfs ((3GdbGgQI(B: s (3ecJHI GdTQhb(B, s, 1998)
(3GdYbhO hGdOjhf ZjQ PGJ GdQHG (B1-(3GdHjhY (B2- (3GdeTGQcGJ CMcGe GdQHhGJ (B1- (3NWGH GdMXQ (B2-(3LRGAGJ GdJMQje CSHGH JMQje GdQHhGJ (B1- (3Mce JMQje GdQHG YfO ZjQ GdeSdejf (B2- (3MceI JMQje QHG GdbQV aj GdGSdGe (B3- (3Mce QHhGJ GdHjYs
Keywords: (3GdQHGs; (3GdeYGedGJ GdHfcjIs; (3QHhGJ HjYs; (3QHhGJ bQhVs